2020
DOI: 10.1002/ece3.6685
|View full text |Cite
|
Sign up to set email alerts
|

Linking behavioral thermoregulation, boldness, and individual state in male Carpetan rock lizards

Abstract: Mechanisms affecting consistent interindividual behavioral variation (i.e., animal personality) are of wide scientific interest. In poikilotherms, ambient temperature is one of the most important environmental factors with a direct link to a variety of fitness‐related traits. Recent empirical evidence suggests that individual differences in boldness are linked to behavioral thermoregulation strategy in heliothermic species, as individuals are regularly exposed to predators during basking. Here, we tested for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 142 publications
(205 reference statements)
0
15
2
Order By: Relevance
“…When studying the effects of Hepatozoon sp. in lacertids, Horváth et al (2016Horváth et al ( , 2020 identified a positive correlation between boldness and intensity of infection, with boldness increasing gradually with the intensity of infection.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…When studying the effects of Hepatozoon sp. in lacertids, Horváth et al (2016Horváth et al ( , 2020 identified a positive correlation between boldness and intensity of infection, with boldness increasing gradually with the intensity of infection.…”
Section: Discussionmentioning
confidence: 96%
“…The presence of multiple parasites in the same system also adds an extra layer of complexity, with mixed infections producing different effects than single infections of either parasite taxa involved (e.g. Marzal et al, 2017), although this aspect often remains uninvestigated (Horváth et al, 2020;Paranjpe et al, 2014). Furthermore, the lack of a resolved phylogeny and related taxonomy of haemogregarine parasites of reptiles (Megía-Palma et al, 2023a;Parejo-Pulido et al, 2023) and widespread reliance on a single, slow-evolving molecular marker (18S rRNA) to screen for haemogregarines means that parasite diversity present in these systems cannot be fully assessed and is likely to be underestimated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral variation is observed in diverse species and behavioral modalities ( Byrne et al, 2004 ; Elnitsky and Claussen, 2006 ; Cauchard et al, 2013 ; Horváth et al, 2020 ). In zebrafish, even complex neuromodulatory processes such as startle habituation display inter-individual variation with distinguishable ‘habituation types’ ( Pantoja et al, 2016 , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inter-individual variation, or individuality, is a hallmark of nearly all animal species and contributes to the population’s fitness and ability to adapt when confronted with environmental change ( Dingemanse et al, 2004 ; Klein et al, 2017 ; Horváth et al, 2020 ). One form of inter-individual variation is sensory and motor biases.…”
Section: Introductionmentioning
confidence: 99%